Acaricide resistance status of Rhipicephalus (Boophilus) microplus and Hyalomma anatolicum collected from Haryana - SHYMA, K P; KUMAR, SACHIN; SANGWAN, A K; SHARMA, ANIL KUMAR; NAGAR, GAURAV; RAY, D D; GHOSH, SRIKANTA (The Indian Journal of Animal Sciences, 2013)
Rhipicephalus (Boophilus) microplus and Hyalomma anatolicum are the commonest tick species in India infesting cattle and buffaloes and cause significant economic losses to dairy and leather industries by adversely affecting the milk production and quality of hides. Tick control strategy involves mainly the use of synthetic acaricides which results into development of acaricide resistance. In the present study, the tick samples were collected from organized and unorganized farms of Hisar (HSR) and Fatehabad (FTH) districts of Haryana state to determine the status of development of acaricide resistance. The discriminating doses (DD) of deltamethrin, cypermethrin and diazinon were established against reference susceptible IVRI-I (national registration no. NBAII/IVRI/BM/1/1998) and IVRI-II (national registration no. NBAII/ IVRI/HA/1/1998) lines of Rhipicephalus (Boophilus) microplus and Hyalomma anatolicum, respectively, using adult immersion and larval packet tests. The results indicated that FTH isolates of R (B) microplus and H anatolicum developed resistance against all the 3 acaricides while the HSR isolates of both the tick species are slowly developing resistance. The data on field status of acaricide resistance in two sampled districts of Haryana will be helpful to adopt suitable strategy to overcome the process of development of resistance in ticks.